Doctorate at the Faculty of Architecture of VGTU: development and tendencies of evolution in the European context - Navickienė, Eglė (Journal of Architecture and Urbanism, 2013)
The article deals with doctoral dissertations prepared and defended at the Faculty of Architecture at current Vilnius Gediminas Technical University in spite of changes of its institutional subordination. It deepens into fields of scientific research investigated during doctoral studies that are considered an important part of research in architecture. The tendencies of evolution of doctorate at the Faculty of Architecture of VGTU are contextualised in architectural research and doctoral studies in architectural research and education institutions both in Lithuania and abroad. During the Soviet times, Lithuanian architects had a possibility to prepare and defend dissertations for a scientific degree of candidate of architectural sciences either at the Faculty of Architecture at Kaunas Polytechnic Institute (afterwards – at Vilnius Engineering Building Institute) or at institutions of architectural research and education in the Soviet Union, outside Lithuania, depending if Lithuanian institutions had the right to educate the aspirants for scientific degree and the right to defend their dissertations. It mostly influenced the dynamics of scientific degrees obtained (see Fig. 1). Architecture was defined as an autonomous research field under the Soviet classification and it helped to shape the identity of the discipline: its width, specific methods and questions. Architectural dissertations of Soviet times were rigorously specialised and empiric, closely connected with practice, deepening into urban issues more than architectural ones (see Fig. 2). Since 1998, architecture loses its integrity and becomes a subfield of Art Critics in Humanities. Since then doctoral dissertations defended at the Faculty of Architecture of VGTU investigate architectural history, theory and critics according traditional methodologies of humanities including interdisciplinary contexts; fundamental academic research dominates. Recent international dynamic changes in both doctoral studies and architectural research directs for the impact of research beyond academia generating more efficient contribution to architectural research and innovation related to ideas, forms, techniques, materials and practices based upon technological advances for the so-called society of knowledge; one of the means is creating various forms of doctorates. Nevertheless, the present situation of doctorate at the Faculty of Architecture of VGTU is not supportive for tuning to new tendencies – revision of national classification of research towards integrity of architecture field, and also introduction of a program of research by design, priorities for innovative, practice-embedded, interdisciplinary, future-oriented research in doctorate at the school might create much more positive medium for the progress. Article in Lithuanian. Doktorantūra VGTU Architektūros fakultete: raida ir kaitos tendencijos Europos kontekste Santrauka. Straipsnyje nagrinėjama doktorantūros (aspirantūros) Vilniaus Gedimino technikos universiteto Architektūros fakultete, nepaisant jo kitusios institucinės priklausomybės, raida. Pagrindinis dėmesys skiriamas apgintų disertacijų mokslinių tyrimų kryptims ir pobūdžiui kaip sudėtinei architektūros mokslo daliai, jų raidą ir kaitos tendencijas siejant su procesais kitose šalyse. Apžvelgiamos šiame amžiuje vykstančios aktualios dinamiškos permainos doktorantūros studijų sampratoje ir architektūros mokslo raidoje kaip architektūros doktorantūros studijų kaitą formuojančiuose veiksniuose. Naujų požiūrių kontekste įvertinamos doktorantūros studijų VGTU Architektūros fakultete pokyčių galimybės. Reikšminiai žodžiai: architektūros doktorantūra, architektūros aspirantūra, architektūros mokslas, daktaro disertacija, VGTU Architektūros fakultetas.